2009
DOI: 10.1001/archsurg.2009.167
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and the Risk of Surgical Site Infections in Elderly Patients Undergoing Elective Surgery

Abstract: Statin use is not associated with an altered risk of surgical site infection. Prevention efforts should be directed toward other evidence-based strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…Evaluation of the 40 studies showed that 21 studies [12], [13], [14], [15], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33] were investigating the prophylactic effect of statin treatment on infections and 19 investigating the therapeutic effect [12], [16], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50]. All the prophylactic studies were excluded from the meta-analysis since the patients did not have a bacterial infection at baseline in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the 40 studies showed that 21 studies [12], [13], [14], [15], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33] were investigating the prophylactic effect of statin treatment on infections and 19 investigating the therapeutic effect [12], [16], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50]. All the prophylactic studies were excluded from the meta-analysis since the patients did not have a bacterial infection at baseline in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies investigated the association between statin treatment and post operative infections after cardiac surgery [14], [25], [31], herniorraphy [22] or any elective surgery [15]. Only one of these studies showed a marginally favourable effect of statin and the over-all impression from these studies is that statins have no convincing prophylactic effect on post-operative infections.…”
Section: Resultsmentioning
confidence: 99%
“…16,21,28 Four were singlecenter studies, 19,21,29 and 2 were population-based studies. 18,28 Statin exposure ascertainment was based on a review of admission medication list 19 and prescription databases 18,21,28 and was not available in 2 studies. 16,29 Infectious outcomes included surgical site infections within 30 days, 18,28 serious infections (sepsis), 21,29 and any postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
“…Los factores intrínsecos de los pacientes son: la complejidad de sus enfermedades, el estado nutricional, el tabaquismo, la obesidad, y la vejez. (15,16,17) En esta investigación, se encontró que los factores que más afectaron a los pacientes fueron: 9.5%, hipertensión y estancia hospitalaria prolongadas; 8.3%, diabetes; 7.1%, consumo de SPA; 4.8%, desnutrición, procesos vasculares o anemia y un 3.6%, enfermedades mentales. También Por todo lo anterior, las enfermedades concomitantes en muchos procesos patológicos tienen un efecto negativo en la cicatrización de heridas.…”
Section: Resultados Y Discusiónunclassified